Edukasi Deteksi Tanda Bahaya Kehamilan Dengan Pemanfaatan Buku Kia Di Posyandu Desa Batursari Kecamatan Sirampog - Ahmad Ridlo; Firda Febriana S; Dwi Aryani; Laela Septiani; Dewi Nur B; Iqlima Fristy W; Endang Aguskristiana (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Pregnancy is a natural process, but if you do not receive proper care during pregnancy it can cause morbidity and even death in the mother. In Indonesia, the maternal mortality rate is still quite high and still below the SDGs (Sustainable Development Goals) targets. The causes of maternal death can be reduced and can be prevented through quality care, one of which is early detection of complications during pregnancy. Apart from that, pregnant women must also know about the danger signs of pregnancy by making maximum use of the KIA Book which contains information about Maternal and Child Health. If the mother knows about the danger signs within herself, the pregnant woman will be more aware of her condition.